(untitled) (Research, Society and Development, 2019)
This study aimed to find a dose of powder prepared from the Moringa Oleífera seed, which is efficient in removing turbidity from water used for human consumption in the rural community of Capela Branca, located in the city of Bela Vista de Minas. A solution was prepared with the plant seed. The experiment was carried out in a Jar Test, where the respective quantities of the prepared solution were first added to each jar of the solution: 5 mL, 10 mL, 15 mL, 20 mL, 25 mL and 30 mL. The solution initially added to the jars was added to the respective amounts: 20 mL, 40 mL, 60 mL, 80 mL, 100 mL and 120 mL. Afterwards the solution was again raised to: 30 mL, 60 mL, 90 mL, 120 mL, 150 mL and 180 mL. Since in the first three experiments there was no efficiency in turbidity removal, the jars were emptied and only 4 of them were filled again for the new test. In each of the 4 jars were added respectively: 0.2160g, 0.432g, 0.648g and 0.884g of the Moringa Oleifera seed powder together with 10 ml of the initially prepared solution. It was possible to notice that the third jar, where 0.648 g of Moringa Oleífera seed powder was added, demonstrated the efficiency of the turbidity removal of 2L of water. It is concluded that the amount of the powder that guarantees turbidity removal efficiency (0.648g) is equivalent to approximately 3 crushed seeds, and higher or lower doses do not work efficiently to remove turbidity.